The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/icb.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

In vivo functional mapping of the conserved protein domains within murine Themis1

Abstract: Thymocyte development requires the coordinated input of signals that originate from numerous cell surface molecules. Although the majority of thymocyte signal initiating receptors are lineage-specific, most trigger ‘ubiquitous’ downstream signaling pathways. T-lineage specific receptors are coupled to these signaling pathways by lymphocyte-restricted adapter molecules. We and others recently identified a new putative adapter protein, Themis1, whose expression is largely restricted to the T lineage. Mice lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…2e ), indicating that the cysteine residues in the CABIT domains are not essential for regulating the PTP activity of SHP-1. This is consistent with previous observations that retrovirally encoded THEMIS-C-A can rescue the DP to SP developmental block in Themis −/− thymocytes 20 . These results demonstrated that the THEMIS CABIT modules directly inhibit SHP-1 PTP activity and that the conserved core cysteine is not required for this function.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2e ), indicating that the cysteine residues in the CABIT domains are not essential for regulating the PTP activity of SHP-1. This is consistent with previous observations that retrovirally encoded THEMIS-C-A can rescue the DP to SP developmental block in Themis −/− thymocytes 20 . These results demonstrated that the THEMIS CABIT modules directly inhibit SHP-1 PTP activity and that the conserved core cysteine is not required for this function.…”
Section: Resultssupporting
confidence: 93%
“…Although THEMIS CABIT modules can bind directly to SHP-1, experimental data strongly suggest that the interaction of THEMIS with GRB2 is important for its in vivo function 12 , 18 , 20 . Co-binding of SHP-1 and THEMIS to GRB2 brings these proteins into close proximity and may facilitate and stabilize their direct interaction.…”
Section: Discussionmentioning
confidence: 99%
“…GRB2, via its SH2 domain, recruits THEMIS to the scaffolding transmembrane T cell adapter Linker for Activation of T cells (LAT) upon TCR engagement [8, 9, 11]. The THEMIS:GRB2 interaction is required for THEMIS in vivo activity [9, 10, 12] indicating that recruitment of THEMIS to LAT by GRB2 is essential for its function.…”
Section: The Fog Begins To Clearmentioning
confidence: 99%
“…THEMIS proteins lacking either the PRS [9, 10, 12] or the NLS [10, 12] were unable to rescue T cell maturation in Themis −/− mice. As described in the text, the PRS is required for binding of THEMIS to the cytosolic adapter GRB2.…”
Section: The Fog Begins To Clearmentioning
confidence: 99%
See 1 more Smart Citation